„When I Die in My Personal Life, I Become Wiser in Helping Others“: Psychotherapists’ Experiences of Bereavement and It’s Impact on Their Work with Clients - Monkevičiūtė, Elena; Vaštakė, Marija (Psichologija, 2024)
The article presents the significance of the experience of bereavement for psychotherapists in their therapeutic work. This issue has not been studied much in the world and has not been raised in Lithuania yet. Paradoxically, the „psychotherapist working on his/her own“ has not been an interesting object of research so far, and so far researchers are mainly interested in the effectiveness of the psychotherapy, the question how psychotherapist feels after the crisis experience and how it affects his/her work remains in the shadows. Thus, the aim of the research presented in this paper is to uncover and systematically describe the implications of psychotherapists’ experience of bereavement for their work with psychotherapy clients. A qualitative research strategy was chosen for the study, data were collected using in-depth semistructured interviews, and analysed using Thematic Analysis. Seven psychotherapists who had experienced the loss of a loved one during the course of their psychotherapeutic work participated in the study. Three themes and seven subthemes were identified in the study, revealing the multilayered nature of experiences in their psychotherapeutic work. Although all the psychotherapists had integrated the loss of a loved one in one way or another and felt personally grown up, this had undoubtedly left traces in their therapeutic work and was experienced as a personal and professional challenge.
Keywords: bereavement experience of psychotherapists; bereavement; psychotherapy process